(untitled) - Susskind, Richard (Oxford, 1998)
This book, required reading for all lawyers and others working in the field, demonstrates that the future of law is digital. Susskind shows how and why Information Technology is radically altering and will continue to alter the practice of law and the administration of justice. For this paperback edition, he has added a substantial new preface which expands upon many of his central themes and takes account of likely developments in technology. Susskind's message to lawyers remains stark: in order to guarantee a stake in the legal system of the future, they must adapt their working practices or die. His message for everyone else is empowering: people can now demand radically improved legal services, and if lawyers cannot provide them, many others will.
Keywords: Law,Practice of law,Information technology; Automation,Automation